International consensus recommendations for the optimal prioritisation and distribution of surgical services in low-income and middle-income countries: a modified Delphi process. Issue 1 (24th January 2023) - Henry, Jaymie A; Reyes, Ana M; Ameh, Emmanuel; Yip, Cheng-Har; Nthumba, Peter; Mehes, Mira; Lelchuk, Ashley; Hollier, Larry; Waqainabete, Ifereimi; Abdullah, Noor Hisham; Alliance, The; Hill, Andrew; et al.
Abstract : Objectives: To develop consensus statements regarding the regional-level or district-level distribution of surgical services in low and middle-income countries (LMICs) and prioritisation of service scale-up. Design: This work was conducted using a modified Delphi consensus process. Initial statements were developed by the International Standards and Guidelines for Quality Safe Surgery and Anesthesia Working Group of the Global Alliance for Surgical, Obstetric, Trauma and Anesthesia Care (G4 Alliance) and the International Society of Surgery based on previously published literature and clinical expertise. The Guidance on Conducting and REporting DElphi Studies framework was applied. Setting: The Working Group convened in Suva, Fiji for a meeting hosted by the Ministry of Health and Medical Services to develop the initial statements. Local experts were invited to participate. The modified Delphi process was conducted through an electronically administered anonymised survey. Participants: Expert LMIC surgeons were nominated for participation in the modified Delphi process based on criteria developed by the Working Group. Primary outcome measures: The consensus panel voted on statements regarding the organisation of surgical services, principles for scale-up and prioritisation of scale-up. Statements reached consensus if there was ≥80% agreement among participants. Results: Fifty-three nominated experts from 27 LMICs voted on 27 statements in two rounds. Ultimately, 26 statements reached consensus and comprise the current recommendations. The statements covered three major themes: which surgical services should be decentralised or regionalised; how the implementation of these services should be prioritised; and principles to guide LMIC governments and international visiting teams in scaling up safe, accessible and affordable surgical care. Conclusions: These recommendations represent the first step towards the development of international guidelines for the scaling up of surgical services in LMICs. They constitute the best available basis for policymaking, planning and allocation of resources for strengthening surgical systems.